Analisis Visual Rias Wajah Karakter Topeng Kelana dalam Karya The Tale of Kelana - Revi Dian Permata; Ifa Nurhayati; Ade Novi Nurul Ihsani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the level of suitability of the makeup work of the Kelana Mask character in the work of The Tale of Kelana based on the assessment of expert panelists. The study uses a descriptive quantitative method with the object in the form of a character makeup work that adapts the visual characteristics of the Kelana Mask of Cirebon. The research subjects consisted of three expert panelists in the field of makeup and performing arts. Data were collected through a Likert scale questionnaire of 1-4 with 15 statements covering five indicators, namely makeup application techniques, color composition, creativity and innovation, theme suitability, and visual impact. Data were analyzed using descriptive percentage analysis. The results showed that the work obtained a total score of 166 out of a maximum score of 180 with a feasibility percentage of 92.22% in the very good category. In detail, the makeup application technique and color composition each obtained 94.44%, creativity and innovation 91.67%, theme suitability 88.89%, and visual impact 91.67%. These findings indicate that the makeup work was deemed technically and visually feasible, and was able to maintain the main visual characteristics of Kelana, so that the character appears strong and easily recognizable as a representation of the Kelana Mask.